2021
DOI: 10.1002/advs.202100548
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Growth of In‐Oxo Chain Based Metal‐Porphyrin Framework Thin Film for High‐Sensitive Photodetector

Abstract: The potential of metal-organic frameworks (MOFs) for applications in optoelectronics results from a unique combination of interesting photophysical properties and straightforward tunability of organic and inorganic units. Here, it is demonstrated that using MOF approach chromophores can be assembled into well-ordered 1D arrays using metal-oxo strands as lead structure, and the resulting porphyrinic rows exhibit unique photophysical properties and allow the realization of highly sensitive photodetectors. A porp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…Recently, MOF thin films (named SURMOFs) prepared by a liquid-phase epitaxial (LPE) layer-by-layer (lbl) method have exhibited numerous advantages including controlled growth orientation, homogeneous surface, tunable thickness and compactness, etc., and greatly promote the applications of MOF materials in photoelectronic devices, which will offer an opportunity for fabricating MOF-based photodetector devices. For example, recently, a few cases of porphyrin-based MOF thin films have emerged to study the photodetection properties by loading C 60 , controlling the growth orientation and adjusting the thickness. , However, tuning metalloporphyrinic ligands in such an MOF thin film to study the photodetection performance has not been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, MOF thin films (named SURMOFs) prepared by a liquid-phase epitaxial (LPE) layer-by-layer (lbl) method have exhibited numerous advantages including controlled growth orientation, homogeneous surface, tunable thickness and compactness, etc., and greatly promote the applications of MOF materials in photoelectronic devices, which will offer an opportunity for fabricating MOF-based photodetector devices. For example, recently, a few cases of porphyrin-based MOF thin films have emerged to study the photodetection properties by loading C 60 , controlling the growth orientation and adjusting the thickness. , However, tuning metalloporphyrinic ligands in such an MOF thin film to study the photodetection performance has not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…For example, recently, a few cases of porphyrin-based MOF thin films have emerged to study the photodetection properties by loading C 60 , controlling the growth orientation and adjusting the thickness. 46,47 However, tuning metalloporphyrinic ligands in such an MOF thin film to study the photodetection performance has not been reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, the advent of MOF films greatly promotes the applications of MOF materials in optical/electric devices and sensors. Particularly, surface-coordinated MOF films (SURMOFs) prepared by a liquid-phase epitaxial (LPE) layer-by-layer (lbl) method have been considered as a good candidate for optical device applications , due to the strong adhesion to the substrate surface, controllable orientation, and highly transparent homogeneous film, etc. Very recently, 3D porphyrinic MOF films prepared by the LPE lbl method have emerged to study the third-order NLO effect by controlling the thickness, loading a guest, and adjusting the wavelength or laser intensity. , Nevertheless, the oriented 2D porphyrinic SURMOFs possessing abundant π–π interactions between layers have not been reported for an NLO study.…”
mentioning
confidence: 99%
“…[19][20][21][22] In recent years, there have been many reports on MPFs. [23][24][25][26][27] Furthermore, the optical nonlinearity and ultrafast NLO response of MPFs have become a major research focus. Porphyrin molecules with an 18 π-electron conjugated system, as well as its derivatives, are considered to be some of the most promising NLO materials because of their excellent NLO properties and good chemical stability.…”
Section: Introductionmentioning
confidence: 99%